Short-Term Efficacy of Tenofovir Alafenamide in Acute-On-Chronic Liver Failure: A Single Center Experience - Zhiqin Li; Ruirui Zhu; Jianxia Dong; Yinghui Gao; Jingya Yan (SAGE Publishing, 2024)
Background: Patients with acute-on-chronic liver failure (ACLF) who take entecavir (ETV) and tenofovir disoproxil fumarate (TDF) experience a reduction in hepatic events and mortality. The effectiveness of tenofovir alafenamide (TAF) was not well investigated. This study was aim to compare the antiviral efficacy and mortality between TAF and ETV in patients with ACLF caused by the hepatitis B virus (HBV). Methods: One hundred and six patients with HBV-ACLF who received TAF (25 mg/day) and ETV (0.5 mg/day) for 12 weeks were analyzed. The primary endpoints were overall mortality and liver transplantation (LT) at week 12. Biochemical responses, virologic responses, mortality, drug safety, and side effects were evaluated. Results: At 4 and 12 weeks of TAF treatment, patients showed significantly higher HBV-DNA reduction ( P  < .001), higher HBV-DNA undetectability rates ( P  < .001), and lower HBV DNA levels ( P  < .001) in serum. Lower Child-Turcotte-Pugh (CTP) scores ( P  = .003) were observed at 4 weeks in the TAF group, although the CTP scores showed no difference between TAF group and ETV group at 12 weeks ( P  = 1.143). Lower alanine aminotransferase (ALT) levels of patients in the TAF group at week 4 and 12 were observed ( P  = .023 and P  < .0001, separately). The mortality of TAF group was lower after 4 weeks of treatment ( P  = .038); however, the 2 groups had similar mortality rates at week 8 and 12. Among the causes of death in HBV-ACLF patients, we found the same incidence of liver-related problems in both groups ( P  > .05). Conclusions: This study showed that ACLF patients with chronic HBV infection treated with TAF had a rapid decline in HBV DNA, a higher rate of ALT reduction and improved CTP scores compared to the ETV group, thereby improving patient survival.